Biesiada, muzyka, taniec, czyli współczesne wesele jako forma zabawy w powiecie garwolińskim - Woźniak, Małgorzata (Zeszyty Wiejskie, 2025)
Polish traditional wedding shows varieties of cultural patterns, that’s why it contains many elements, that are very interesting to research from anthropological point of view. Depending on researcher’s interestings and cultural context, it was considered from many different perspectives. But we live in fast developing world, socio-cultural context is changing, so there is also needed the reconsideration of some elements of culture. This is why I wanted to show transformation of functions of wedding rituals at the polish village. The change of magical symbolism for the entertaining symbolism. My idea was to show contemporary wedding ritual more as a party, where the old mixes with the new. What elements of tradition survived and how they were transformed. Underlining the influence of fashion and pop culture I wanted to prove that saving traditional form and idea, general function of wedding ritual has been changed. Today, traditional polish wedding is more a party than ritual, party that needs long time prepartion, money, party that marks social status of organizers and that is under the influence more of fashion than tradition.